PERSEPSI MAHASISWA AKUNTANSI: FAKTOR - FAKTOR YANG MEMPENGARUHI MINAT PEMILIHAN PROFESI SEBAGAI AKUNTAN PUBLIK (STUDI EMPIRIS: MAHASISWA JURUSAN AKUNTANSI UNTAN) - Nicholas Christiansen -; Ayu Umyana -; Juanda Astarani (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
This research aims to determine the influence of accounting ability and professional image on interest in choosing a profession as a public accountant among students majoring in accounting at UNTAN with self-efficacy as a moderating variable to see how self-efficacy influences accounting ability and professional image on interest in choosing a profession as a public accountant. . The research population focuses on students majoring in accounting at FEB UNTAN. Where samples were taken using the purposive sampling method. Testing in this research uses descriptive statistical analysis, data quality testing, classical assumption testing, multiple regression analysis, moderated regression analysis, and model testing to study hypotheses. The data was processed using the SPSS version 27 application. The research results showed that simultaneously, accounting skills and professional image influenced the interest in choosing a profession for accounting students majoring in accounting at FEB UNTAN. Partially, accounting ability and professional image both have a negative and significant influence on interest in choosing a profession as a public accountant. On the other hand, self-efficacy slightly strengthens each independent variable towards the dependent variable. Keywords: Accounting Ability; Professional Image; Interest as Public Accountant; Self-Efficacy